2019
DOI: 10.1017/jog.2019.82
|View full text |Cite
|
Sign up to set email alerts
|

A full Stokes ice-flow model to assist the interpretation of millennial-scale ice cores at the high-Alpine drilling site Colle Gnifetti, Swiss/Italian Alps

Abstract: The high-Alpine ice-core drilling site Colle Gnifetti (CG), Monte Rosa, Swiss/Italian Alps, provides climate records over the last millennium and beyond. However, the full exploitation of the oldest part of the existing ice cores requires complementary knowledge of the intricate glacio-meteorological settings, including glacier dynamics. Here, we present new ice-flow modeling studies of CG, focused on characterizing the flow at two neighboring drill sites in the eastern part of the glacier. The3-D full Stokes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 62 publications
(129 reference statements)
1
29
3
Order By: Relevance
“…Given the high variability in the accumulation rate, three ice cores may not be enough to fully represent the site, besides, ice core data are biased due to the fact they are drilled preferentially in the north flank, where accumulation and radiation are lower. While the modelled average annual accumulation is in the range of the ones estimated for the north flank of CG (Licciulli et al, 2020), the model is not able to reproduce the observed spatial variability. This would require to consider the effect of topography on wind speed and the spatial variation in solar radiation.…”
Section: Snow Accumulationcontrasting
confidence: 68%
See 2 more Smart Citations
“…Given the high variability in the accumulation rate, three ice cores may not be enough to fully represent the site, besides, ice core data are biased due to the fact they are drilled preferentially in the north flank, where accumulation and radiation are lower. While the modelled average annual accumulation is in the range of the ones estimated for the north flank of CG (Licciulli et al, 2020), the model is not able to reproduce the observed spatial variability. This would require to consider the effect of topography on wind speed and the spatial variation in solar radiation.…”
Section: Snow Accumulationcontrasting
confidence: 68%
“…Even though the site is characterized by high precipitation totals, accumulation in the saddle is considerably lower and highly variable over the glacier surface due to wind erosion, with values ranging from about 0.15 • 10 3 kg m −2 y −1 to 1.2 • 10 3 kg m −2 y −1 depending on the wind exposure (Alean et al, 1983;Lüthi and Funk, 2000;Licciulli et al, 2020). Alean et al (1983) measured the accumulation at CG between 17 August 1980 and 23 July 1982 with a network of 30 stakes.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Two examples are given based on ice originating from 1960 and 1950. tion area of glaciers have been used to infer the depth-age relationship of ice cores (e.g., Lüthi and Funk, 2000;Schwerzmann, 2006;Winski et al, 2017). Recently, Licciulli et al (2019) improved this approach by implementing a full ice flow model.…”
Section: Introductionmentioning
confidence: 99%
“…Lüthi and Funk, 2000;Schwerzmann, 2006;Winski et al, 2017). Recently, Licciulli et al (2019) improved this approach by combining to an ice flow model. 2 https://doi.org/10.5194/tc-2020-142 Preprint.…”
Section: Introductionmentioning
confidence: 99%